The Case for Using Evidence-Based Guidelines in Setting Hospital and Public Health Policy - Francis, Ross H.; Mudery, Jordan A.; Tran, Phi; Howe, Carol; Jacob, Abraham (Frontiers in Surgery, 2016)
Objective: Hospital systems and regulating agencies enforce strict guidelines barring personal items from entering the Operating Room - touting surgical site infections and patient safety as the rationale. We sought to determine whether or not evidence supporting this recommendation exists by reviewing available literature. Background data: Rules and guidelines that are not evidence based may lead to increased hospital expenses and limitations on healthcare provider autonomy Methods: PubMed, Embase, Scopus, Cochrane Library, Web of Science, and CINAHL were searched in order to find articles that correlated personal items in the OR to documented surgical site infections. Articles that satisfied the following criteria were included: (1) studies looking at personal items in the OR such as handbags, purses, badges, pagers, backpacks, jewelry phones, and eyeglasses, etc., but not just operating room equipment; and (2) the primary outcome measure was infection at the surgical site. Results: Seventeen articles met inclusion criteria and were evaluated. Of the 17, the majority did not determine if personal items increased risk for surgical site infection. Only 1 article examined the correlation between a personal item near the operative site and surgical site infection, concluding that wedding rings worn in the OR had no impact on surgical site infections. Most studies examined colonization rates on personal items as potential infection risk; however, no personal items were causally linked to surgical site infection in any of these studies. Conclusion: There is no objective evidence to suggest that personal items in the OR increase risk for surgical site infections.